A Computational Characterization of 2, 2′-bis(trifluoromethyl)-[1, 1′-biphenyl]-4, 4′-diamine Iodine Dopant for Improving Power-Conversion Efficiency of Perovskite Solar Cells. (1st November 2022) - Slanina, Zdeněk; Uhlík, Filip; Feng, Lai; Adamowicz, Ludwik
Abstract : The paper presents ongoing density-functional theory (DFT) computational support to research of hybrid perovskite solar cells to facilitate their understanding at molecular level. Very recently, doping by a iodine salt, namely 2, 2′-bis(trifluoromethyl)-[1, 1′-biphenyl]-4, 4′-diamine iodine BFBAI2, has been described that improves the power conversion efficiency and enhances device stability. As structural characteristics of BFBAI2 are not well known, they are supplied here through DFT calculations for both BFBAI2 monomer and dimer. The geometry optimizations are performed at the M06-2X/3-21G level, and energetics is refined with the M06-2X/Def2QZVP treatment. The dimerization potential-energy change is calculated as −6.2 kcal/mol. BFBAI2 exhibits highly non-uniform charge distribution, i.e., it is a clearly polar system that can strongly modulate surface conditions when adsorbed. The adsorption-energy gain for BFBAI2 on CsPbI3 perovskite is DFT evaluated as −13.2 kcal/mol.